2017
DOI: 10.1021/acs.jpca.7b09563
|View full text |Cite
|
Sign up to set email alerts
|

The Hydrogen Abstraction Reaction H2S + OH → H2O + SH: Convergent Quantum Mechanical Predictions

Abstract: The hydrogen abstraction reaction HS + OH → HO + SH has been studied using the "gold standard" CCSD(T) method along with the Dunning's aug-cc-pVXZ (up to 5Z) basis sets. For the reactant (entrance) complex, the CCSD(T) method predicts a HSH···OH hydrogen-bonded structure to be lowest-lying, and the other lower-lying isomers, including the two-center three-electron hemibonded structure HS···OH, have energies within 2 kcal/mol. The similar situation is for the product (exit) complex. With the aug-cc-pV5Z single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(51 citation statements)
references
References 73 publications
(138 reference statements)
4
46
1
Order By: Relevance
“…The OH radical was detected in the ISM more than 5 decades ago, in 1964 . Besides astrochemistry, it is also important in combustion chemistry. Hence, a variety of studies featuring the interaction of the OH radical, especially with H 2 O, have been reported earlier. The geometries and interaction energies obtained in this work are very much similar to earlier results obtained, thereby validating the present work.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The OH radical was detected in the ISM more than 5 decades ago, in 1964 . Besides astrochemistry, it is also important in combustion chemistry. Hence, a variety of studies featuring the interaction of the OH radical, especially with H 2 O, have been reported earlier. The geometries and interaction energies obtained in this work are very much similar to earlier results obtained, thereby validating the present work.…”
Section: Resultssupporting
confidence: 87%
“…Some studies featuring potential energy surfaces of some interstellar/astrochemical gas-phase chemical reactions usually report a pre-reactant complex, which facilitates further reaction. Such studies have especially been performed with the OH radical, because it is relevant in not just astrochemistry but also combustion chemistry. The pre-reactant complex in the case of OH radicals is held together by weak chemical interactions, mainly hydrogen bonding.…”
Section: Introductionmentioning
confidence: 99%
“…The energy disposal pattern with about 50% of reaction energy released as H 2 O and HOD vibrations supports such mechanism. Partitioning of energy differs from that for the OH reaction with H 2 S, although all the reactions are presumed to have weak H‐hydrogen bonding between water and radical, including HS, in the exit channel. This observation supports the claim that such adducts in the exit channel are not very important for vibrational energy disposal in H‐atom transfer reactions …”
Section: Discussionmentioning
confidence: 99%
“…The rate constants for reaction (4) do not give linear Arrhenius plots, and experimental values for E a can be obtained only for certain temperature ranges. A curved Arrhenius plot of H 2 S was analyzed in the experimental study of Lafage et al, who recommended E a = 0.78 kcal mol −1 for temperatures above 294 K. 20 Recent theoretical works 21,22 confirm a non-Arrhenius behavior of the OH + H 2 S reaction with predicted ab initio barrier heights (difference between the energies of transition state and reactants) of 0.70 kcal mol −1 (CCSD(T) aug-cc-pV5Z level corrected for zero point vibrational energy 21 ) and 0.82 kcal mol −1 (MC-QCISD/3 level 22 ). Assignment of <E av > for reaction (4) was made taking E a = 0.75 kcal mol −1 .…”
Section: Vibrational Distributionsmentioning
confidence: 99%
See 1 more Smart Citation